THE IMPACT OF CORPORATE RISK GOVERNANCE AND INVESTMENT DECISION ON ASSET AND EQUITY RETURNS OF NIGERIAN NON-LIFE INSURANCE FIRMS - Muritala, Taiwo A (J-MACC : journal of management and accounting, 2024)
This study examines the impact of risk management and investment practices on the financial performance of non-life insurance companies in Nigeria, using a panel data set of ten selected firms from 2009 to 2022. Employing descriptive statistics, unit root tests, correlation analysis, and panel regression models, the study investigates the relationships between risk management practices (RM), investment practices (IP), and key financial performance indicators, namely Return on Assets (ROA) and Return on Equity (ROE). The results indicate that risk management practices do not have a statistically significant effect on either ROA or ROE, while investment practices are significantly negatively related to ROA, highlighting the potential risks associated with aggressive investment strategies. These findings underscore the need for context-specific risk governance and prudent investment policies within the Nigerian insurance sector to enhance financial stability and performance. The study contributes to the understanding of financial performance determinants in emerging markets and offers policy implications for regulators and insurance firms aiming to strengthen operational efficiency and shareholder value.